2009
DOI: 10.1159/000255166
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine TORCH Screening Warranted in Neonates with Lenticulostriate Vasculopathy?

Abstract: Background: Congenital infections are associated with a wide spectrum of clinical symptoms, including lenticulostriate vasculopathy (LSV). Objective: To determine the relationship between LSV and congenital infections, as diagnosed by TORCH serology and viral culture for cytomegalovirus (CMV). Methods: All neonates with LSV admitted to our neonatal intensive-care unit from 2004 to 2008 were included in the study. Results of maternal and neonatal TORCH testing were evaluated. Results: During the study period, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…In the same report, authors summarized 10 prior studies evaluating congenital infections in neonates with LSV. In this series, the overall incidence of congenital infections was 7% (32/442) of all neonates tested for infection [54]. Another review of 70 infants found 3 infants with congenital infection (4%, 2 HIV-infected, 1 congenital toxoplasmosis) [14].…”
Section: Clinical Managementmentioning
confidence: 63%
See 1 more Smart Citation
“…In the same report, authors summarized 10 prior studies evaluating congenital infections in neonates with LSV. In this series, the overall incidence of congenital infections was 7% (32/442) of all neonates tested for infection [54]. Another review of 70 infants found 3 infants with congenital infection (4%, 2 HIV-infected, 1 congenital toxoplasmosis) [14].…”
Section: Clinical Managementmentioning
confidence: 63%
“…As a result, routine screening for congenital infections in infants with LSV has fallen out of favor [9]. de Jong et al [54] reviewed 80 infants with LSV cared for in their neonatal intensive care unit during a 5-year period and did not find evidence of congenital infection in any of them. In the same report, authors summarized 10 prior studies evaluating congenital infections in neonates with LSV.…”
Section: Clinical Managementmentioning
confidence: 99%
“…For example, LSV has been reported to be present on 0.4% of screening cranial ultrasounds in all neonates admitted to the NICU [18], 0.3-4% in neonates who had an ultrasound scan for a clinical indications [3,13,[19][20][21][22] and 5-32% in preterm neonates receiving an ultrasound scan to screen for suspected pathology [5,[23][24][25][26]]. An upward trend in incidence has been reported in recent studies [5,26,27], which might reflect nothing more than a growing awareness of this finding on neonatal cranial ultrasound.…”
Section: Incidence Of Lsvmentioning
confidence: 99%
“…To date, most published reports of LSV are retrospective reviews [6,11,13,[19][20][21]23,24,28,29] or case reports of varying size [7,14,16,[30][31][32][33][34][35][36][37][38] with the diagnosis frequently made by a single radiologist without confirmation. Existing prospective studies are limited in number and sample size, resulting in conflicting observations and conclusions [18,22,26].…”
Section: Challenges Evolved In the Fieldmentioning
confidence: 99%
“…This resulted in the recommendation that all neonates with LSV should be screened for congenital infection. However, since then, several studies questioned this association and failed to show the same results [4][5][6][7][8]. LSV has been linked to various infectious and non-infectious etiologies.…”
mentioning
confidence: 99%